Estudo e aplicações da evolução diferencial - Oliveira, Giovana Trindade da Silva (2006)
In the last few decades, the application of optimization in engineering problems has grown considerably. There are various optimization methods and the performance of each one depends on the type of problem considered. The natural methods, which are based on probabilistic rules, have been widely studied. The purpose of this work is to present a detailed study of the natural optimization method called Differential Evolution and its strategies. A theoretical formulation is presented. In this work, a revision of Genetic Algorithms and Simulated Annealing is made. These techniques are employed to compare their results to those obtained with Differential Evolution. Classic mathematical functions and some problems of engineering are used in order to verify the efficiency of the studied technique. The Differential Evolution is applied with effectiveness in multi-objective optimization problems with and without the presence of constraints including two complex robotic problems.